Expression of mitochondrial uncoupling protein 3 and adenine nucleotide translocase 1 genes in developing rat heart: putative involvement in control of mitochondrial membrane potential - Skárka, Libor; Bardová, Kristina; Brauner, Petr; Flachs, Pavel; Jarkovská, Daniela; Kopecký, Jan; Ostádal, Bohuslav (Journal of molecular and cellular cardiology, 2003)
Postnatal maturation of the heart depends on the switch from glycolytic to oxidative metabolism and it is associated with decreasing tolerance to oxygen deprivation. Therefore, changes in composition and function of cardiac mitochondria during postnatal development require detailed characterization. Left-ventricular myocardium of prenatal, and 1-, 2-, 5-, 10-, 20-, 28-, 50-, 60-, and 90-d-old male Wistar rats was studied. The expression of uncoupling proteins (UCPs), adenine nucleotide translocase (ANT), and peroxisome proliferator-activated receptor alpha (PPARalpha) genes was characterized by northern blotting (UCP2), real-time quantitative RT-PCR (UCP2, UCP3, ANT1, ANT2, and PPARalpha), and by immunoblotting (UCP3). In isolated mitochondria, cytochromes a + a(3) were quantified by a spectrophotometry, and mitochondrial membrane potential (MMP) was measured using Rhodamine 123 (by spectrofluorimetry and flow cytometry). The specific content of cytochromes in mitochondria increased two-fold between birth and day 30, similarly, as the expression of ANT1 and PPARalpha genes. Postnatal activation in the expression of UCP2, UCP3, ANT1 and PPARalpha genes resulted in the expression maxima between days 20 and 30. The content/expression declined following day 20 (UCP2, UCP3, and PPARalpha) or 30 (cytochromes and ANT1), while expression of ANT2 declined continuously during the first month of life. In 1-d-old animals a single population of mitochondria with a relatively high MMP was observed; with increasing age, a second population of mitochondria with a significantly lower MMP appeared. The results support the view that mitochondrial energy conversion in heart changes during ontogeny and suggest the involvement of UCP3 and/or ANT1 in the control mechanism.
Keywords: srdce; novorozená zvířata; Transcription Factors; Mitochondria; translokátor adeninových nukleotidů 2; membránové potenciály; Adenine Nucleotide Translocator 1; transkripční faktory; myokard; Membrane Potentials; zvířata; Rats; Animals, Newborn; uncoupling protein 3; Ion Channels; transportní proteiny; mužské pohlaví; mitochondrie; Adenine Nucleotide Translocator 2; Heart; iontové kanály; Rats, Wistar; translokátor adeninových nukleotidů 1; receptory cytoplazmatické a nukleární; krysa rodu Rattus; potkani Wistar; Animals; Carrier Proteins; Mitochondrial Proteins; Myocardium; mitochondriální proteiny; Male; Receptors, Cytoplasmic and Nuclear; Uncoupling Protein 3